â€œMUSLIM MODERATâ€ DALAM KONTEKS SOSIAL-POLITIK DI INDONESIA - Hairul Puadi (JURNAL PUSAKA, 2014)
â€œModerate Muslimsâ€ is a problematic, in the sense that it is too wide for the debate and the plurality of meanings. Everything depends entirely on the perspective, mindset, or even a subjective interests of the maker of meaning itself. This paper describes the debate over the meaning, sociological reality and the role of â€œmoderate Muslimsâ€ in Indonesia. With a sociological explanation, this paper concluded that in the context of socio-political constellation today, the meaning of the term â€œmoderate Muslimâ€ can actually be identified easily. The term refers to the majority of Muslims who live and move to and in the midst of the society, seeking a change from ground, and reject religious extremism, violence, and terrorism. The existence of a moderate wing of Islamic organizations such as NU and Muhammadiyah is a guarantee for the establishment of democracy optimism in Indonesia in the midst of â€œthe stormâ€ of radical Islamic groups today.Keywords: Moderate Muslims, radicalism, democracy